Reanimating industrial spaces
1 online resource (254 pages)
Keywords: "Reanimating Industrial Spaces explores the relationships between people and the places of former industry through approaches that incorporate and critique memory-work. The chapters in this volume consider four broad questions: What is the relationship between industrial heritage and memory? How is memory involved in the process of place-making in regards to industrial spaces? What are the strengths and pitfalls of conducting memory-work? What can be learned from cross-disciplinary perspectives and methods? The contributors have created a set of diverse case studies (including iron-smelting in Uganda, Puerto Rican sugar mills and concrete factories in Albania) which examine differing socio-economic contexts and approaches to industrial spaces both in the past and in contemporary society. A range of memory-work is also illustrated: from ethnography, oral history, digital technologies, excavation, and archival and documentary research"--